The Gender Wage Gap across Life: Effects of Genetic Predisposition Towards Higher Educational Attainment - Alex Bryson; Tim Morris; David Bann; David Wilkinson (Institute of Labor Economics (IZA), 2024)
Using two polygenic scores (PGS) for educational attainment in a biomedical study of all those born in a single week in Great Britain in 1958 we show that the genetic predisposition for educational attainment is associated with labour market participation and wages over the life- course for men and women. Those with a higher PGS spend more time in employment and full-time employment and, when in employment, earn higher hourly wages. The employment associations are more pronounced for women than for men. Conditional on employment, the PGS wage associations are sizeable, persistent and similar for men and women between ages 33 and 55. A one standard deviation increase in the PGS is associated with a 6-10 log point increase in hourly earnings. However, whereas a 1 standard deviation increase in the PGS at age 23 raises women's earnings by around 5 log points, it is not statistically significant among men. These associations are robust to non-random selection into employment and to controls for parental education. Our results suggest that genetic endowments of a cohort born a half century ago continued to play a significant role in their fortunes in the labor market of the 21st Century.
Keywords: I26; J31; J16; J24; 330; gender wage gap; employment; educational attainment; polygenic score; National Child Development Study